Jewish American identity and erasure in pop art - Mednicov, Melissa L. (New York, NY : Routledge, 2024)
"This volume focuses on Jewish American identity within the context of Pop art in New York City during the 1960s to reveal the multivalent identities and selves often ignored in Pop scholarship. Melissa L. Mednicov establishes her study within the context of prominent Jewish artists, dealers, institutions, and collectors in New York City in the Pop 1960s. Mednicov incorporates the historiography of Jewish identity in Pop art - the ways by which identity is named or silenced - to better understand how Pop art made, or marked, different modes of identity in the sixties. By looking at a nexus of the art world in this period and the ways in which Jewish identity was registered or negated, Mednicov is able to further consider questions about the ways mass culture influenced Pop art and its participants - and, to a larger extent, formed further modes of identity. The book will be of interest to scholars working in art history, Jewish studies, and American studies"--
Introduction and before pop : Jewish American identity in New York City -- Roy Lichtenstein : the missing Jewish pop artist -- The Jewish Museum in the sixties -- Gallerists, collectors, and art historians in the sixties : class, mobility, and Jewish American identity -- Edges of pop -- Contemporary connections and conclusions.
Keywords: Art and society -- New York (State) -- New York -- History -- 20th century; Jews -- New York (State) -- New York -- Identity; Jews -- United States -- Identity; Pop art -- United States; ART / History / Modern (late 19th Century to 1945); ART / History / Contemporary (1945-)